Managing for success : the Farnsworth formulas - Farnsworth, Terry (London ; New York : McGraw-Hill, 1981)
The aim of this book is to alert you to these hazards and to provide you with a route-map which will enable you to reach your objective in the shortest possible time.
hza 28/09/2018
Loans
Keywords: Organization; Success in business; Executives